Algebra teachers’ questions and quandaries – Swedish and Finnish algebra teachers discussing practice - Kilhamn, Cecilia; Röj-Lindberg, Ann-Sofi (NOMAD Nordic Studies in Mathematics Education, 2019)
Taking the teachers’ own practices as a point of departure, this study investigates what areas of mathematical knowledge algebra teachers brought up in collegial discussions and how they used their knowledge in acts of decompressing, trimming and bridging. The discussions centered around aspects of teaching and learning school algebra previously shown to be problematic, but gave rise to mathematical quandaries, revealing gaps in the teachers’ own understanding of the mathematical content. The study implies that the ability to unpack a mathematical concept is essential in algebra teaching and that teachers may need external input concerning mathematical knowledge to enable development in pedagogical content knowledge.